1995
DOI: 10.1006/viro.1995.1247
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A and FK506 Block Induction of the Epstein-Barr Virus Lyric Cycle by Anti-Immunoglobulin

Abstract: The Epstein-Barr virus (EBV) BZLF1 gene is expressed early upon induction of the viral lytic cycle and its protein product is unique in its ability to disrupt viral latency in some latently infected cell lines. Anti-immunoglobulin (anti-Ig) treatment of the Burkitt's lymphoma cell line Akata, which bears surface IgG, has previously been shown to synchronously induce transcription of the BZLF1 gene (K. Takada and Y. Ono, 1989, J. Virol. 63, 445-449). We have previously shown that anti-Ig induction of Akata cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…It has been previously reported that anti-Ig induction of the EBV lytic cycle in Akata cells can be blocked by the immunosuppressants cyclosporine and tacrolimus (11). As shown in Fig.…”
Section: Resultsmentioning
confidence: 77%
“…It has been previously reported that anti-Ig induction of the EBV lytic cycle in Akata cells can be blocked by the immunosuppressants cyclosporine and tacrolimus (11). As shown in Fig.…”
Section: Resultsmentioning
confidence: 77%
“…each of these events, though all the events have yet to be analyzed simultaneously in one experimental system. In Akata cells, EBV lytic cycle activation, triggered by crosslinking of the B-cell antigen receptor, can be blocked by cyclosporine A and FK506 which inhibit the Ca 2Ï© /calmodulindependent protein kinase pathway (27). In B95-8 cells, EBV lytic cycle activation mediated by treatment with TPA is blocked by bisindoylmaleimide, a specific inhibitor of protein kinase C (29).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation and hence activation of latently infected cells appears to be a critical component of the reactivation of gammaherpesviruses. This hypothesis has been further shown by the inhibition of the signaling cascade following stimulation with anti-Ig antibodies with the immunosuppressive drugs cyclosporine A and FK506, which prevents induction of EBV lytic replication (10). These results suggest that the full downstream signaling cascade is necessary to drive reactivation.…”
mentioning
confidence: 83%